Financial literacy and related outcomes: the role of financial information sources - Sabri, Mohamad Fazli; Cheng Xi, Eugene Aw (Universiti Malaysia Sarawak * Faculty of Economics and Business, 2019)
The purpose of this study is to investigate consumers’ preferences in different financial information sources and their impact on financial literacy. This study also aims to examine the impacts of financial literacy on the amount of income allocated for investment, as well as the hiring of a financial planner. A large-scale survey was conducted in Malaysia, and a total of 2000 usable responses were collected. The results showed that (1) there is a negative effect of preference in media, family and peers as financial information sources on financial literacy; (2) there is a positive effect of preference in financial planners as a financial information source on financial literacy; (3) consumers who use the Internet as their main financial information source exhibit higher financial literacy; (4) financial literacy positively influences the amount of income allocated for investment; and (5) financial literacy is negatively related to the likelihood of hiring a financial planner. This study provides empirical evidence for practitioners to improve financial literacy by encouraging the use of appropriate financial information sources. This study also offers an understanding on consumers’ financial behaviors, which result from different levels of financial literacy.